Core decompression versus other joint preserving treatments for osteonecrosis of the femoral head: a meta-analysis - Sadile, Francesco; Bernasconi, Alessio; Russo, Sergio; Maffulli, Nicola (British medical bulletin, 2016)
Osteonecrosis of femoral head (ONFH) leads to hip osteoarthritis (HOA); among joint preserving treatments (JPT), the role of core decompression (CD) is still debated. We assessed the efficacy of CD compared with all other JPT in delaying the natural osteonecrosis evolution to HOA. Following the PRISMA checklist, the Medline and Scopus databases were searched. Fifteen- to 70-year-old subjects with ONFH with a minimum follow-up of 24 months were considered. The outcomes evaluated were patient clinical status, radiographic progression and total hip arthroplasty (THA) or further surgery (FS) need. Risk ratio (RR) was calculated for every outcome reported. RCT, CCT and prospective studies were included. A total of 12 studies (776 patients) met the inclusion criteria. Clinical outcome (RR = 1.14; 95% CI 0.58-2.32; P = 0.05), radiographic progression (RR = 1.64; 95% CI 1.14-2.35; P = 0.05) and the need for THA/FS (RR = 1.52; 95% CI 0.95-2.45; P = 0.05) suggested a slight superiority of other JPT compared with CD. High heterogeneity of the primary investigations was the main limitation of our study. The efficacy and effectiveness of core decompression for ONFH are, at best, no better than other joint preserving strategies. The more recent scientific evidence seems to suggest that such procedure is less successful than other joint preserving strategies. Further studies are needed to identify the best therapeutic approach to the ONFH.